Genetic Analysis of Father-Daughter Incest Using Multifaceted STR Markers and Study of Inheritance Pattern of Alleles - Dash, Hirak Ranjan; Gautam, Ila; Singh, Anil Kumar; Shrivastava, Pankaj (Current Forensic Science, 2023)
Background Two cases involving father-daughter incest, a rare report in the Indian population, have been analyzed in the current study. STR markers on both autosomal and sex chromosomes were employed to expound the cases. Objective The objective of this study is to confirm the identity of the fetus as a product of father-daughter incest and to study the inheritance pattern of alleles in such cases. Methods Autosomal, X, and Y chromosomal analyses were performed to confirm the identity of the fetus. Statistical analyses were carried out to strengthen the evidentiary value of the obtained results. Results In both cases, the aborted fetus was found to be the product of an incestuous father-daughter relationship. The probability of paternity as well as maternity was found to be >99.9999% in both cases. Analysis of other paternity and forensic parameters also substantiated the inclusion of the alleged individuals. Father-daughter incest had a tremendous effect on the genome as evidenced from the dramatical decrease in unrelated alleles between father/child [16.66% (Case 1), 20% (Case 2)] and mother/child [26.66% (Case 1), 21.66% (Case 2)]. Genetic evidence also suggested an increased biallelic match i.e., 26.66% (Case 1) and 33.33% (Case 2) between mother and fetus, which are at par/ above the normal siblings’ values i.e., 26.66%. Conclusion A significant increase in the percentage of homozygous alleles (53.33% in both cases) was observed in the product of father-daughter incest. Both daughters share the same X chromosome from the father, which also suggested the case to be of father-daughter incest. Similarly, the same Y-STR profile between the male fetus and alleged father confirmed the correct pattern of inheritance of the Y chromosome in this case.
Keywords: DNA Fingerprinting